Understanding the models of community hospital rehabilitation activity (MoCHA): a mixed method study - Gladman, John R.F.; Buckell, John; Young, John; Smith, Andrew; Hulme, Claire; Saggu, Satti; Godfrey, Mary; Enderby, Pam; Teale, Elizabeth; Longo, Roberto; Gannon, Brenda; Holditch, Claire; et al. (BMJ Publishing Group Ltd, 2017)
Introduction